2023
DOI: 10.3390/biomedicines11030893
|View full text |Cite
|
Sign up to set email alerts
|

Naturally Occurring N-Terminal Fragments of Bovine Milk Osteopontin Are Transported across Models of the Intestinal Barrier

Abstract: Osteopontin (OPN) is a bioactive integrin-binding protein found in high concentrations in milk, where it is present both as a full-length protein and as several N-terminally derived fragments. OPN resists gastric digestion, and via interaction with receptors in the gut or by crossing the intestinal barrier into circulation, ingested milk OPN may influence physiological processes. The aim of this study was to investigate OPN interaction with intestinal cells and its transport across models of the intestinal bar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…This development holds the potential to provide a more accurate biomarker for evaluating the risk of DKD in individuals with DM [15]. Another study, although in a different scenario, demonstrated that milk ntOPN bounded intestinal cells most effectively and was transported across the intestinal membrane indicating that proteolytic processing of OPN to form ntOPN increases its biological activity [273]. These findings support the efficacy of OPN/ntOPN as a therapeutic target in DKD.…”
Section: Opn-mediated Fibrosis In Dkdmentioning
confidence: 76%
“…This development holds the potential to provide a more accurate biomarker for evaluating the risk of DKD in individuals with DM [15]. Another study, although in a different scenario, demonstrated that milk ntOPN bounded intestinal cells most effectively and was transported across the intestinal membrane indicating that proteolytic processing of OPN to form ntOPN increases its biological activity [273]. These findings support the efficacy of OPN/ntOPN as a therapeutic target in DKD.…”
Section: Opn-mediated Fibrosis In Dkdmentioning
confidence: 76%
“…Resistance to digestive proteases is primarily attributed to the glycosylated and conserved threonine residues close to the Arg-Gly-Asp integrin-binding sequence ( 44 , 54 , 57 , 58 ). In vitro evidence suggests that intact OPN and/or fragments can cross the intestinal barrier via transcytosis ( 59 ), and dietary bmOPN has been detected in the plasma of rodents and humans ( 23 , 55 , 60 ), demonstrating absorption.…”
Section: Absorption Distribution Metabolism and Excretion Of Milk Ost...mentioning
confidence: 99%
“…In an in vitro study, the bovine milk OPN fragment Trp 27 -Phe 151 , generated by pepsin cleavage, was shown to cross models of the intestinal barrier via transcytosis [85]. The naturally occurring N-terminal OPN fragments bound intestinal cells more effectively and were more effectively transported across the membrane models compared to fulllength OPN.…”
Section: Digestion and Uptake Of Milk Osteopontinmentioning
confidence: 99%